The Effects of Good Governance Principles: Accountability, Transparency, and Participation on Public Trust in Village Funds Management - Umi Umairah Suhardi; Ulung Pribadi; Zainuddin Losi (Universitas Pendidikan Ganesha, 2023)
The number of village budget deviations in several regions in Indonesia has increased every year, one of which is in the Polewali Mandar Regency. Therefore, the application of the principles of Good Governance is expected to be able to overcome these problems, which in turn can improve the welfare of people's lives. The purpose of this study was to examine the effect of applying the principles of good governance (accountability, transparency, and participation) as independent variables and community trust in managing village funds as the dependent variable. This study uses mixed methods research with data analysis techniques using Vosviewer with journal database google Scholar obtained through publish or perish by using keywords good governance and village funds to visualize the topic of good governance network in the management of village funds in Indonesia by year of issue (2017-2022). Furthermore, using the SEMpls analysis technique as a tool to test validity using village apparatus and the community of Binuang District, Polewali Mandar Regency as samples. Sampling using the method of purposive sampling, so 100 respondents were obtained. The results of this study indicate that transparency, accountability, and participation have a positive and significant effect on community trust in the village government in managing village funds. That is, the more accountable and transparent the village government is in managing village funds, the greater public trust will be. If the community has more trust in the village government, the community will more actively participate in village fund management.